A DEIXIS ANALYSIS OF A SONG LYRICS ENTITLED “LOVER” - Sofiatul Fadilah; Setya Resmini (IKIP Siliwangi, 2021)
This research is a qualitative research which aims to analyze the kinds of dominant deixis in the song lyrics entitled ‘Lover’. The data collected from the lyrics then classified into types of deixis according to Levinson (1983:62) theory. The classification of the data then analyzed by relating the deixis to the references/meaning from the lyrics. The result of this research found that there are 51 deixis found in the lyrics consist of 39 personal deixis, 7 temporal deixis, and 5 spatial deixis. Most of personal deixis in ‘Lover’ lyric refer to the speaker itself which are encoded by first singular personal deixis like I and My. While for first plural personal deixis which is We, mostly refer to the speaker. Finally, this research is expected to provide an understanding of deixis and the context that is conveyed by the speaker. Keywords: Deixis, Pragmatics, Song Lyrics